2012
DOI: 10.1111/j.1755-0998.2012.03147.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of six candidate DNA barcoding loci in Ficus (Moraceae) of China

Abstract: Ficus, with about 755 species, diverse habits and complicated co-evolutionary history with fig wasps, is a notoriously difficult group in taxonomy. DNA barcoding is expected to bring light to the identification of Ficus but needs evaluation of candidate loci. Based on five plastid loci (rbcL, matK, trnH-psbA, psbK-psbI, atpF-atpH) and a nuclear locus [internal transcribed spacer (ITS)], we calculated genetic distances and DNA barcoding gaps individually and in combination and constructed phylogenetic trees to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 45 publications
2
57
0
Order By: Relevance
“…; CBOL Plant Working Group ; Li et al . ). Of the coding regions, matK provided higher species resolution (73.6%) than rbcL (60.5%) (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…; CBOL Plant Working Group ; Li et al . ). Of the coding regions, matK provided higher species resolution (73.6%) than rbcL (60.5%) (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…This distribution pattern was observed in other large genera such as Ficus L. (Moraceae) (Li et al . ) and Parnassia L. (Parnassiaceae) (Yang et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Liu, Zhang, et al (2012) showed a 100% identification using the psbA-trnH sequence in 38 species from the genus Rhododendron. Li, Chen, Wang, and Xiong (2012) discovered that the efficiency of the ITS sequence is 70% when examining 63 species in the genus Ficus. Yang, Wang, Möller, Gao, and Wu (2012) used ITS + psbA-trnH sequences to identify 30 species from the genus Parnassia with 90% efficiency.…”
Section: Introductionmentioning
confidence: 99%